What he wants for Christmas - Jackson, Brenda (Brenda Streater) (Jackson, Brenda (Brenda Streater) Westmoreland legacy: the Outlaws, 2021)
When a holiday blizzard traps him with his ex things really heat up! It's been ten years since she broke his heart, but Leslie Cassidy's elegance still stuns rugged Alaskan executive Sloan Outlaw. Now, thanks to a ruthless enemy targeting Leslie's company, Sloan can use his wealth and influence for something nice - and something naughty. He'll save her company - if she'll spend a week with him at his luxurious winter retreat! But when a snowstorm keeps them cabin-bound, this notorious Outlaw will discover that getting what he wants for Christmas might be more than he bargained for.